Challenging perceptions about rural practice using narratives: a living library approach in medical education - Perez, Grace; Malhi, Rebecca; Bressler, Kamiko; Monaghan, Melissa; Johnston, Aaron (Frontiers in Medicine, 2024)
The shortage of physicians in rural Canada is a continuing challenge. Canadian medical schools have adapted strategies to increase the supply of rural physicians. This study appraises the effectiveness of the living library (also called Human Library Ó ) in medical education, as an avenue for medical and pre-medical students to engage in dialogue with rural health professionals. Similar to a conventional library, readers check out books, except that 'books' are human volunteers willing to share relevant personal experiences, and 'readers' are the learners. The reading is the personal interaction between human books and students through narratives of experiences. Using our program "The Library of Life -Stories of Rural Medicine" (TLoL), we aimed to provide students with better understanding of rural life and practice through narratives.Methods: This is a mixed methods study, using pre-and post-event surveys. Statistical comparisons were done using Wilcoxon and McNemar's tests. Thematic analysis was used to explore students' expectations of TLoL and to describe their experience and key takeaways.Results: Most of the participants were from an urban background, had low familiarity with rural medicine and only 44% would consider a rural career prior to TLoL. After TLoL, we observed improvements in: (i) envisioning rural medicine as career option (p=0.009), (ii) appreciation of rural living (p=0.013), (iii) need for rural physicians (p<0.001) and (iv) rural practice consideration (p=0.001). Themes from students' motivations for participation were: (i) students' curiosity, interest, and (ii) their willingness to engage in dialogue with the human books. Themes from the key takeaways were that TLoL allowed students: (i) to walk in a rural professional's shoes, enabling them to see "rural" in a new light, and (ii) to self-reflect and gain a sense of personal growth.Conclusions: Students made gains in attitudes and perceptions towards rural practice. Narratives have the power to challenge held beliefs around rural practice and life. We can encourage students to consider things that traditional medical teaching may not. TLoL can be an effective learning modality in medical education to provide information about rural medicine, in combination with learning opportunities such as rural block rotations and longitudinal clinical clerkship immersions.